Two Tongues, One Brain: Imaging Bilingual Speech Production - Simmonds, Anna J.; Wise, Richard J.; Leech, Robert (Frontiers in Psychology, 2011)
This review considers speaking in a second language from the perspective of motor-sensory control. Previous studies relating brain function to the prior acquisition of two or more languages (neurobilingualism) have investigated the differential demands made on linguistic representations and processes, and the role of domain-general cognitive control systems when speakers switch between languages. In contrast to the detailed discussions on these higher functions, typically articulation is considered only as an underspecified stage of simple motor output. The present review considers speaking in a second language in terms of the accompanying foreign accent, which places demands on the integration of motor and sensory discharges not encountered when articulating in the most fluent language. We consider why there has been so little emphasis on this aspect of bilingualism to date, before turning to the motor and sensory complexities involved in learning to speak a second language as an adult. This must involve retuning the neural circuits involved in the motor control of articulation, to enable rapid unfamiliar sequences of movements to be performed with the goal of approximating, as closely as possible, the speech of a native speaker. Accompanying changes in motor networks is experience-dependent plasticity in auditory and somatosensory cortices to integrate auditory memories of the target sounds, copies of feedforward commands from premotor and primary motor cortex and post-articulatory auditory and somatosensory feedback. Finally, we consider the implications of taking a motor-sensory perspective on speaking a second language, both pedagogical regarding non-native learners and clinical regarding speakers with neurological conditions such as dysarthria.